The role of the verb assists on the construction of the time composes in French and in English Le rôle du verbe auxiliaire dans la construction du temps composé en français et en anglais - Hamid, Adnan Jabar (International Journal of Humanities and Education Development (IJHED), 2021)
An auxiliary verb is a verb that serves another verb to form a compound tense. In the compound tense, the auxiliary verb plays an important role. The auxiliary verb, however, is devoid of meaning and only serves to indicate the tense in the sentence. This article strives to carry out a comparative analysis of the dynamic in French and in English. The intention is to distinguish auxiliary verbs in French and their usage. Examples with verbs in different compound tenses have been cited in both languages